If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(9+3x)=-18
We simplify the equation to the form, which is simple to understand
2(9+3x)=-18
Reorder the terms in parentheses
+(+18+6x)=-18
Remove unnecessary parentheses
+18+6x=-18
We move all terms containing x to the left and all other terms to the right.
+6x=-18-18
We simplify left and right side of the equation.
+6x=-36
We divide both sides of the equation by 6 to get x.
x=-6
| 2x+5=6x | | 7x-40+7x^2=0 | | X^4+3x^3-11x^2+99x+8=0 | | -4k+17= | | 16t^2+24t+9=0 | | f+9.42=37.68 | | 5(b+1)=4(b+3) | | 8a+48= | | n^2+n-182=0 | | -9x-6=-4-10x | | y+.2=.4(y+5) | | 11-p=19 | | (2x^2-x-3)-(x+1)=y | | -5x+15=5 | | -2x=o | | (-5-6)+(-1-4)= | | 2(x-2)+2x=4(x+8)-36 | | 2(4y-3)-8=4+2y | | 6t+25=20-t | | .5m+2(.75m-1)=.25m+6 | | (2x^2-x-3)+(x+1)=y | | (6,4),(-5,-1)= | | 90=10p-99 | | x^2-2x+28=0 | | 3(3m+4)=6m-3 | | -1/2=y-1 | | 2x+x+2=169 | | .66b+2.97=.66b+2.97 | | .66b+2.97=.66+2.97 | | 3x+9=4x+4 | | 7(x+6)=6(x-6)+x | | 45b-15=45b+45 |